Mixed ionic-electronic conductivity, redox behavior and thermochemical expansion of Mn-Substituted 5YSZ as an interlayer material for reversible solid oxide cells - Natoli, Alejandro (2021)
Manganese-substituted 5 mol.% yttria-stabilized zirconia (5YSZ) was explored as a prospective material for protective interlayers between electrolyte and oxygen electrodes in reversible solid oxide fuel/electrolysis cells. [(ZrO2)0.95(Y2O3)0.05]1-x[MnOy]x (x = 0.05, 0.10 and 0.15) ceramics with cubic fluorite structure were sintered in air at 1600 °C. The characterization included X-ray diffraction (XRD), scanning electron microscopy (SEM)/energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), thermogravimetry and dilatometry in controlled atmospheres, electrical conductivity measurements, and determination of oxygen-ion transference numbers by the electromotive force (EMF) technique. Mn-substituted 5YSZ solid solutions exhibit variable oxygen nonstoichiometry with manganese cations in a mixed 2+/3+ oxidation state under oxidizing conditions. Substitution by manganese gradually increases the extent of oxygen content variation on thermal/redox cycling, chemical contribution to thermal expansion and dimensional changes on reduction. It also deteriorates oxygen-ionic conductivity and improves p-type electronic conductivity under oxidizing conditions, leading to a gradual transformation from predominantly ionic to prevailing electronic transport with increasing x. Mn2+/3+→Mn2+ transformation under reducing atmospheres is accompanied by the suppression of electronic transport and an increase in ionic conductivity. All Mn-substituted 5YSZ ceramics are solid electrolytes under reducing conditions. Prolonged treatments in reducing atmospheres, however, promote microstructural changes at the surface of bulk ceramics and Mn exsolution. Mn-substituted 5YSZ with 0.05 ≤ x < 0.10 is considered the most suitable for the interlayer application, due to the best combination of relevant factors, including oxygen content variations, levels of ionic/electronic conductivity and thermochemical expansion.